Query Portals: Dynamically Generating Portals for Entity-Oriented Web Queries - Agrawal, Sanjay; Chakrabarti, Kaushik; Chaudhuri, Surajit; Ganti, Venkatesh; König, Arnd Christian; König, Arnd Christian; Xin, Dong (International Conference on Management of Data (SIGMOD 2010), 2010)
Many web queries seek information about named entities (such as products or people). Web search engines federate such entity-oriented queries to relevant structured databases; the results of those searches are then returned to the user along with web search results. Current federated approaches have two limitations: (i) they often fail to return important results for a broad class of such entity-oriented queries and (ii) the information they return per entity is often inadequate. In this paper, we present the Query Portals system that addresses these limitations. The Query Portals system dynamically generates a portal for an entity-oriented query. It ﬁrst provides an overview of the relevant entities and further allows users to drill down to gather additional information on these entities. Our architecture uses a judicious combination of pre-processing and query time techniques so that the query portal can be generated eﬃciently.